Adaptability of Polish Red cows to extensive conditions - Witold Chabuz; Paweł Żółkiewski; Wioletta Sawicka-Zugaj; Krzysztof Buczek; Marta Staniec; Sylwester Kowalik; Piotr Rydel; Andrzej Lisowski; Karolina Kasprzak-Filipek (BMC Veterinary Research)
Abstract This study assessed the adaptive capacity of Polish Red cattle, one of the oldest indigenous dual-purpose breeds in Europe, to extensive environmental conditions in north-eastern Poland. Twenty-two pregnant cows (average lactation number: 4.6) were divided into two groups: one maintained in a highly extensive ‘bale grazing’ system (EXT), and the other under traditional housing for suckler cows (TRAD). The experiment was conducted from the onset of winter through to the end of the subsequent pasture season. Parameters assessed included changes in body weight and body condition score (BCS), calf growth performance, milk yield, and haematological and biochemical blood indices. Statistical analysis was performed using independent-samples t-tests and the Mann–Whitney U test (p ≤ 0.05, p ≤ 0.01). Despite challenging environmental conditions in the EXT group, including no shelter and exposure to variable climatic factors, cows maintained body condition and health comparable to the TRAD group. While TRAD group calves showed superior growth (29 kg higher body weight, p ≤ 0.01), EXT group cows exhibited remarkable resilience by supporting calf survival with minimal weight loss (average 4.4 kg loss, less than 1% of initial body weight). Blood parameters remained within physiological ranges for both groups, confirming the breed’s adaptability. These findings provide the first experimental evidence of the adaptability of Polish Red cattle to extensive farming systems, highlighting their potential as a valuable genetic resource for sustainable livestock production under increasing environmental variability. This conclusion has significant implications for the conservation of biodiversity and the development of climate-resilient cattle breeding in Europe.